Experimental Analysis on the Dependence of the Capacitance of Magnetorheological Fluids on Frequency - Zhu, Xuli; Ma, Shanshan; Huang, Haidong; Liu, Zhongling; Sun, Huimin; Teng, Guirong (Frontiers in Materials, 2022)
The capacitance characteristics of magnetorheological fluids (MRFs) were studied experimentally based on simulation analysis. The nonlinear relationship between capacitance of MRFs and electric field frequency was measured by the self-made circuit device. The effects of magnetic induction intensity and particle volume fraction on the capacitance characteristics of MRFs were investigated. The results show that the nonlinear dependence of capacitance of an MRF on frequency induced by the effect of tunnel current decreases with the increase of frequency. The capacitance of an MRF is directly related to the particle structures. The capacitance of the MRF with chain particle structure is greater than that of the MRF with random particle distribution, the smaller the clearance between the adjacent particles, the greater the capacitance of the MRF. The network particle structure and particle contact will reduce the capacitance of an MRF. The capacitance of an MRF increase with the increment of external magnetic field. The capacitance of an MRF with higher particle volume fraction is smaller than that of an MRF with lower particle volume fraction.